2017
DOI: 10.3390/genes8120359
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Hormonal Regulation of Weeping Trait in Salix matsudana

Abstract: Salix matsudana is a large and rapidly-growing tree, with erect or spreading branchlets (upright willow). However, S. matsudana var. pseudomatsudana is one of the varietas, with pendulous branchlets (weeping willow). It has high ornamental value for its graceful pendulous branches. In order to study the molecular basis for this weeping trait, leaves and stems collected at different developmental stages were analyzed using RNA-seq coupled with digital gene expression. Although weeping trees are used worldwide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 58 publications
2
17
0
Order By: Relevance
“…The library was sequenced on an Illumina HiSeq TM 2000 platform (Illumina, San Diego, CA, USA). Transcript quantification from RNA-Seq data was performed in a previous study [46]. In each DGE library, tag sequences were mapped to the reference sequences generated in the RNA-Seq-based transcriptome.…”
Section: Sample Preparation For Transcriptome and Dge Profiling Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The library was sequenced on an Illumina HiSeq TM 2000 platform (Illumina, San Diego, CA, USA). Transcript quantification from RNA-Seq data was performed in a previous study [46]. In each DGE library, tag sequences were mapped to the reference sequences generated in the RNA-Seq-based transcriptome.…”
Section: Sample Preparation For Transcriptome and Dge Profiling Analysismentioning
confidence: 99%
“…The expression of each gene was normalized to the expected number of Fragments Per Kilobase of transcript sequence per Millions base pairs sequenced (FPKM). Quantitative real-time PCR (qRT-PCR) analysis was performed to validate the expression levels of DEGs from RNA-Seq and DGE data in a previous study [46]. Based on the quantification of transcript results, nine pairwise comparisons in six DGE libraries of the two willow species at two developmental stages using two different branch portions were analyzed.…”
Section: Screening Of Differentially Expressed Genes (Degs)mentioning
confidence: 99%
See 1 more Smart Citation
“…In peach, the pl phenotype may be associated with GA signaling and upright branch internodes are shorter than those of weeping branches in peach, implying that the upright type may have a lower GA content 27 . Transcriptional results suggest that GA and auxin play a vital role in controlling the weeping trait in Salix matsudana 28 . Transcriptome analysis of columnar apple trees showed that genes associated with auxin and GA, such as xyloglucan endotransglycosylase (XTH) and gibberellin 2β-dioxygenase 1 (GA2ox1), are located in the Co region linked with the apple column trait 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Since all of the intersectional hybrids investigated in the present study had semi-cascade-type shoots, the shoot pattern in Tricyrtis may be a semi-dominant trait. In Prunus spachiana (Nakamura et al 1994) and Salix matsudana (Liu et al 2017), weeping shoot traits are regulated by the endogenous gibberellin level. It is necessary to analyze the endogenous gibberellin level in Tricyrtis plants with erect-, semi-cascade-and cascadetype shoots.…”
Section: Brachycyrtismentioning
confidence: 99%